FRI0477 Prospective observational study on the evaluation of quality of life in patients affected by enteropathic spondyloarthritis. (15th June 2017) - Chimenti, MS; Conigliaro, P; Polistena, B; Triggianese, P; Ruffa, A; Canofari, C; Cedola, F; Onali, S; Balan, M; Calabrese, E; Petruzziello, C; Spandonaro, F; et al.
Abstract : Background: Enteropathic Spondyloarthritis (ESpA) belongs to the group of Spondyloarthritis (SpA) tipically associated with inflammatory bowel disease (IBD) as Crohn's Disease (CD) and Ulcerative Colitis (UC). Joint pain is the most common (22–33%) and significant extra-intestinal manifestation in patients with IBD and its management requires reumatological and gastroenterological competence in collaboration. No data concerning the Health-related quality of life (HRQoL) have been evaluated in patients affected by ESpA. Objectives: Prospective study was performed in a combined GastroIntestinal and RHEumatologic "GI-Rhe" clinic, in order to evaluate: 1) prevalence and characteristics of articular manifestations in a group of IBD patients; 2) quality of life, state of health and well-being in ESpA patients. Methods: Patients affected by IBD who presented muscolo-skeletal pain between February 2013 and September 2016 (CD 264 and UC 142) were enrolled. New diagnosis, disease management, adverse events as well as laboratory evaluations were assessed every 3 months during the follow-up. Disease activity, function and quality of life in ESpA patients were assessed by ASDAS-CRP, HAQ-S and EuroQol questionnaire. Results: A total of 427 patients were evaluated for joint involvement (Table 1). The prevalence of SpA in IBD patients was 49.6% (n=212: UC 71 (43.3%), CD 141 (53.4%)), suggesting that the majority of patients with IBD who complain arthralgia may have a concomitant SpA. Other rheumatologic diseases were detected in the study population in 215 patients defined as IBD non-SpA. There was a significantly higher prevalence of active intestinal disease in patients with SpA with respect to IBD-non SpA (CD: CDAI>150 in 18.4% vs 8.2% p=0.004; UC: Mayo score >3 in 15.5% vs 0%, p=0.0004). The evaluation of the EuroQoL demonstrated a mean value of 0.59 in IBD-SpA patients and of 0.55 in IBD non-SpA (Figure 1A). In IBD-SpA, the health related status was: decent 69.8%, good 17.9% and bad 9.4%. In IBD-non SpA, the health related status was: decent in 74.8%, good in 17.7% and bad in 7% of patients. In both groups, none of the patients had a neither exceptional nor great perception of QoL. No significant differences were observed between the two groups (Figure 1B-C). Conclusions: The joint clinic facilitates diagnosis and management of SpA and IBD. Although IBD-SpA patients showed higher IBD disease activity than IBD-non SpA one, both groups of patients have a good health related QL. Disclosure of Interest: None declared